Faculty Attitudes and Response to Online Learning in Transnational Higher Education in Qatar: A Promising Future - Saliba, Reya; Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2024)
This paper presents preliminary results from a doctoral thesis investigating faculty attitudes, preparedness, and response to adopting technology-enhanced learning during the 2020-2021 pandemic. The current events that affected teaching and learning worldwide necessitated a re-evaluation of the traditional higher education system and imposed an immediate adjustment to teaching approaches. Using a survey and semi-structured interviews with faculty members teaching at transnational higher education institutions in the state of Qatar, this paper presents the recent pedagogical shift experienced during the pandemic. Using a case study approach, this paper examines the impacts of this shift on student learning from faculty perspective and discusses the implications of this shift on networked learning research and practice. Findings suggest that faculty found online teaching more difficult than previously perceived which encouraged them to be creative and innovative in their teaching approaches. However, there does not seem to be an agreement as to whether online learning is the future of higher education as some faculty still see more value in face-to-face teaching. Furthermore, student assessment is an issue for some faculty. Overall, faculty members seem to appreciate the online teaching experience as it allowed them to try new teaching approaches, use new technologies, and integrate new assessment techniques that they would not consider in their pre-pandemic classes.